1981
DOI: 10.1063/1.525033
|View full text |Cite
|
Sign up to set email alerts
|

Schrödinger equation with time-dependent boundary conditions

Abstract: A Schrödinger equation for a well potential with varying width is studied. Generalized canonical transformations are shown to transform the problem into a time-dependent harmonic oscillator problem submitted to fixed boundary conditions. This transformed problem is solved by a perturbation technique and gives the evolution of the average energy of the system according to the motion of the well. Motions corresponding to a renormalization or compaction group are shown to be solvable by separation of variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 4 publications
0
66
0
1
Order By: Relevance
“…The time dependence in (22)(23), is thus, in a sense, spurious. Consequently, there remains, in fact, only four fundamental arbitrary functions in the linearizable generalized Ermakov system (22)(23), that is, F may be incorporated in C and ρ may be eliminated by the quasi-invariance transformation. It must be stressed, however, that the quasi-invariance transformation is not an essential step in the linearization procedure.…”
Section: Linearization Of Generalized Ermakov Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time dependence in (22)(23), is thus, in a sense, spurious. Consequently, there remains, in fact, only four fundamental arbitrary functions in the linearizable generalized Ermakov system (22)(23), that is, F may be incorporated in C and ρ may be eliminated by the quasi-invariance transformation. It must be stressed, however, that the quasi-invariance transformation is not an essential step in the linearization procedure.…”
Section: Linearization Of Generalized Ermakov Systemsmentioning
confidence: 99%
“…This is manifest in equation (22) where we see, by inspection, that B can account for F . The second and perhaps more interesting remark is that the linearizable generalized Ermakov system (22-23) can be expressed in autonomous form, by means of a quasi-invariance [15,22] transformation…”
Section: Linearization Of Generalized Ermakov Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of such system requires solving the Schrödinger equation with time-dependent boundary conditions. Earlier, the problem of time-dependent boundary conditions in the Schrödinger equation has attracted much attention in the context of quantum Fermi acceleration [12][13][14], although different aspects of the problem were treated by many authors [16][17][18][19][20][21][22][23][24][25][26][27]. Detailed study of the problem can be found in a series of papers by Makowski and co-authors [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the scaling form of V (x, t) in Eq. (1) and the linear form of L(t), separation of variables can be achieved through a series of transformations introduced in [11,12] (see also: [9,10]). One first transforms the coordinate frame into a rescaled frame with a rescaled coordinatex defined bȳ…”
Section: Schrödinger Equation With a Scaling Potentialmentioning
confidence: 99%